An Immunogenic Personal Neoantigen Vaccine for Melanoma Patients - Ott, Patrick A. (Nature, 2017)
Effective anti-tumor immunity in humans has been associated with the presence of T cells directed at cancer neoantigens(1), which are T cell epitopes with tumor-specific expression arising from non-silent somatic mutations. They are highly immunogenic because they are not expressed in normal tissues and hence bypass central thymic tolerance. Although neoantigens were long-envisioned as optimal targets for an anti-tumor immune response(2), their systematic discovery and evaluation only became feasible with the recent availability of massively-parallel sequencing for detection of all coding mutations within tumors, and of machine learning approaches to reliably predict those mutated peptides with high-affinity binding of autologous HLA molecules. We hypothesized that vaccination with neoantigens can both expand pre-existing neoantigen-specific T cell populations and induce a broader repertoire of new T cell specificities in cancer patients, tipping the intra-tumoral balance in favor of enhanced tumor control. Here we demonstrate the feasibility, safety and immunogenicity of a vaccine that targets up to 20 predicted personal tumor neoantigens. Vaccine-induced polyfunctional CD4(+) and CD8(+) T cells targeted 58 (60%) and 15 (16%), respectively, of the 97 unique neoantigens used across patients. These T cells discriminated mutated from wildtype antigens, and in some cases, directly recognized autologous tumor. Of 6 vaccinated patients, 4 had no recurrence at 25 months post-vaccination, while 2 with progressive disease were subsequently treated with anti-PD-1 therapy and experienced complete tumor regression, with expansion of the repertoire of neoantigen-specific T cells. These data provide a strong rationale for further development of this approach, alone and in combination with checkpoint therapies.